2012
DOI: 10.2223/jped.2223
|View full text |Cite
|
Sign up to set email alerts
|

A model-based educational intervention to increase physical activity among Iranian adolescents

Abstract: Objective: To conduct an evaluation of an educational program based on the health promotion model (HPM) and stages of change to improve physical activity (PA) behavior among Iranian adolescents. Methods:This was a group randomized controlled trial with 165 participants in two groups (intervention/control). Data were collected using self-reported questionnaires based upon HPM constructs (benefits and barriers of action, self-efficacy, activity-related affect, interpersonal influences, and situational influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
2
10
1
Order By: Relevance
“…Nevertheless, differences in all HPM constructs, except activity-related affect and social influences, were significant between baseline and follow-up measurements, adolescents in the intervention as compared to the control group were placed in action (70%) or preparation (30%) stages at follow-up, and the results revealed that competing preferences, social norms, role models, and commitment to action plan can significantly predict PA behavior, and the model accounted for 22.5% of the variance in PA [10]. Moreover, a group of pregnant women aged between 15 and 49 years coming to public health facilities to iden- was not significant, also the relationship between the uptake of IPTp and perceived seriousness of malaria infection during pregnancy was not significant, while perception about the duration suggesting up to 95% chance that the uptake of IPTp significantly associated with the duration taken at the health facilities before receiving services, and the attitude of most providers at the ANC facilities 99% chance that the uptake of IPTp significantly associated with perceived attitudes of providers towards pregnant women attending ANC clinics (P = 0.000) [12].…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Nevertheless, differences in all HPM constructs, except activity-related affect and social influences, were significant between baseline and follow-up measurements, adolescents in the intervention as compared to the control group were placed in action (70%) or preparation (30%) stages at follow-up, and the results revealed that competing preferences, social norms, role models, and commitment to action plan can significantly predict PA behavior, and the model accounted for 22.5% of the variance in PA [10]. Moreover, a group of pregnant women aged between 15 and 49 years coming to public health facilities to iden- was not significant, also the relationship between the uptake of IPTp and perceived seriousness of malaria infection during pregnancy was not significant, while perception about the duration suggesting up to 95% chance that the uptake of IPTp significantly associated with the duration taken at the health facilities before receiving services, and the attitude of most providers at the ANC facilities 99% chance that the uptake of IPTp significantly associated with perceived attitudes of providers towards pregnant women attending ANC clinics (P = 0.000) [12].…”
Section: Resultsmentioning
confidence: 94%
“…The 17 research studies that met the inclusion criteria were retrieved and reviewed, where 16 of them used quantitative research methodologies [6]- [21], and one used qualitative methodology [22]. Cross-sectional research design was the most commonly used design in the quantitative studies, and two studies used quasi experimental design [18] [20], and one study used a randomized clinical trial [10] (See Figure 1). …”
Section: Overview Of the Reviewed Studiesmentioning
confidence: 99%
See 3 more Smart Citations